2016
DOI: 10.1007/s13139-016-0438-5
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of SPECT/CT in Parathyroid Lesion Detection in Patients with Thyroid Parenchymal 99mTc-Sestamibi Retention

Abstract: Purpose Parathyroid adenoma detection with dual-phase 99m Tc-sestamibi (MIBI) scintigraphy depends on differential MIBI washout from thyroid. However, autoimmune thyroid disease (AITD) may cause MIBI to be retained in the thyroid gland and reduce parathyroid detection. We evaluated the impact of AITD on MIBI thyroid retention and additional benefit of SPECT/CT in these patients. Methods Dual phase planar MIBI and SPECT/CT was performed on 82 patients. SPECT/CT was performed immediately after delayed planar sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…This could be because patients who underwent DTDP imaging were patients who initially underwent DT imaging and findings from the initial Tc-99m sestamibi and Tc-99m pertechnetate images were deemed insufficient for diagnosis by the nuclear medicine physician on duty thus prompting further delayed imaging, so patients in the DTDP group represented 'difficult' patients which findings were likely to be inconclusive to begin with. Both add-on SPECT and SPECT/CT improved the diagnostic accuracy over planar imaging alone which concurs with previous studies [5,[16][17][18][19]28]. However, SPECT imaging appeared to have a higher diagnostic accuracy than SPECT/CT which is unexpected and contradicts a previous study which demonstrated the superiority of SPECT/CT over SPECT alone [29].…”
Section: Discussionsupporting
confidence: 79%
“…This could be because patients who underwent DTDP imaging were patients who initially underwent DT imaging and findings from the initial Tc-99m sestamibi and Tc-99m pertechnetate images were deemed insufficient for diagnosis by the nuclear medicine physician on duty thus prompting further delayed imaging, so patients in the DTDP group represented 'difficult' patients which findings were likely to be inconclusive to begin with. Both add-on SPECT and SPECT/CT improved the diagnostic accuracy over planar imaging alone which concurs with previous studies [5,[16][17][18][19]28]. However, SPECT imaging appeared to have a higher diagnostic accuracy than SPECT/CT which is unexpected and contradicts a previous study which demonstrated the superiority of SPECT/CT over SPECT alone [29].…”
Section: Discussionsupporting
confidence: 79%
“…Previous literature has demonstrated that the interpretation of parathyroid imaging is more difficult in the setting of autoimmune thyroiditis. 6,9,20 Hwang et al demonstrated increased MIBI retention in the setting of autoimmune thyroid disease. 9 Increased retention of MIBI may lead to impaired detection of abnormal parathyroid tissue and account for the decreased performance of MIBIþP in patients with thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…6,9,20 Hwang et al demonstrated increased MIBI retention in the setting of autoimmune thyroid disease. 9 Increased retention of MIBI may lead to impaired detection of abnormal parathyroid tissue and account for the decreased performance of MIBIþP in patients with thyroiditis. Although we did not examine other imaging modalities in the present study, the utility of other imaging modalities such as 4D-CT in the setting of thyroid disease may also be altered.…”
Section: Discussionmentioning
confidence: 99%
“…The main factor limiting the specificity of dual-tracer imaging is the presence of an underlying thyroid disease, such as Hashimoto’s thyroid disease or multinodular goiter. 22,23 However, some true-positive patients also had evidence of underlying thyroid disease, and both thyroid and parathyroid diseases were found in the pathological assessments of these cases. Moreover, our study suggested that dual-tracer SPECT/CT imaging could significantly reduce the impact of underlying thyroid disease on the diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%